Stress analysis and fatigue life perdiction of a welded hinge connection [compact disc] - 213334 Siow, Chai Siong (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006